FOREIGN AND RUSSIAN EXPERIENCE OF REDUCTION OF CASH PAYMENTS IN THE ECONOMY - A. V. Berdyshev (Вестник университета, 2019)
The need to reduce cash payments in the national economy has been substantiated. The practical experience of economically developed foreign countries to reduce payments in cash has been analyzed. The features of the policy to reduce cash payments in the Russian economy have been designated. Based on the highlighted factors, determining the pace of development of non-cash and electronic transfers, it has been concluded, that the reduction of cash payments in the Russian economy should be based on the optimal combination of regulatory and administrative measures to limit cash payments and the development of the technological base and payment infrastructure.